Analysis of Adverse Reactions Associated with the Use of Crataegus-Containing Herbal Products - Herman J. Woerdenbag; Melissa Ursidae; Corine Ekhart; Martina Schmidt; Annabella Vitalone; Florence P. A. M. van Hunsel (MDPI AG, 2024)
Background/Objectives: Products from various parts of Crataegus species are traditionally applied as a cardiotonic. In Europe and the USA, mainly Crataegus monogyna Jacq. (Lindm.) and Crataegus laevigata (Poir.) DC (synonym Crataegus oxyacantha L.) are used, but worldwide, other Crataegus species are also used. Phytotherapeutic preparations with a standardised content of flavonoids and/or oligomeric procyanidins are commercially available. The products are generally considered as safe and are at most associated with minor and atypical adverse reactions. The aim of this study was to critically assess the information about the safety of Crataegus-containing products in humans. Methods: A scoping review of the literature about adverse reactions associated with Crataegus-containing products was performed. Next, individual case safety reports (ICSRs) were assessed, which were included in VigiBase (the World Health Organisation's global database of adverse event reports for medicines and vaccines) and in the database of the Netherlands Pharmacovigilance Centre Lareb. The findings are discussed in relation to the literature. Results: The scoping review yielded 23 clinical studies with single-herb and 14 with multi-herb preparations, from which only a few minor gastrointestinal and cardiac events had been reported. A total of 1527 reports from VigiBase, from 1970 to 2023, were analysed, as well as 13 reports from Lareb. The most frequently reported adverse reactions belonged to the system organ classes 'gastrointestinal disorders', 'skin and subcutaneous tissue disorders', 'general disorders and administration site conditions', 'cardiac disorders' or 'nervous system disorders'. In 277 reports of VigiBase, a single-herb product was the only suspect for causing the adverse reaction(s). Of these, 12.6% were graded as serious. Conclusions: The results of our study provide deeper insight in the adverse reaction profile of Crataegus-containing products and should contribute to their safe application in the treatment of less severe forms of cardiac failure.